Slope Failures Evaluation and Landslides Investigation Using 2-D Resistivity Method - Nordiana, M.M.; Azwin, I.N. (2016)
Slope failure is a complex phenomenon that may caused to landslides. Buildings and infrastructure such as transportation facilities and pipelines located within the boundaries of a landslide can be damaged or destroyed. Slope failure classification and various factors contributing to the instability using 2-D resistivity survey conducted in Selangor, Malaysia are described. Six 2-D resistivity survey lines with 5 m minimum electrode spacing using Pole-dipole array were performed. The data were processed using Res2Dinv and surfer10 software to evaluate the subsurface characteristics. The 2-D resistivity results show that the subsurface consist of two main zones. The first zone was alluvium or highly weathered with resistivity value of 100-1000 Ωm and depth of >30 m. This zone consists of saturated area with resistivity value of 1-100 Ωm and boulders with resistivity value of 1200-7000 Ωm. The second zone with resistivity value of >7000 Ωm was interpreted as granitic bedrock. The study area was characterized by saturated zones, highly weathered zone, highly contain of sand and boulders that will trigger slope failure in the survey area. On the basis of the case examples described, 2-D resistivity method is categorized into desirable and useful method in determination of slope failure and future assessments.